Developing Business English skills using case studies in the framework of multilevel education - Alexandra V. Radyuk; Valentina Yu. Pankova (Peoples' Friendship University of Russia (RUDN University), 2017)
Modern language teaching practices combine traditional teacher- and student-oriented paradigms. Since language is perceived as a tool that helps achieve practical goals, especially in the realm of professional language studies, a need arises to teach it as an application-oriented instrument. The paper considers the methods of communicative and task-based language training with a particular focus on case studies. While the commonly accepted view holds that case studies are applied at advanced levels only, the study argues that they are applicable at various levels. This argument is justified through a practical experiment involving two student groups taking English for Specific Purposes within Advanced and Pre-Intermediate courses. The article describes the challenges and differences in students' performance and the way their work was assessed. The research states that case studies should be adapted to the level of students' language proficiency to help them naturally take on professional roles and use the language spontaneously. At the same time, attention should be paid to the adequacy of business vocabulary and the dynamism of the training process, in which case appropriate teacher intervention may be necessary. The study concludes that the method can be beneficial in terms of students' future professional activities.